Comprehensive Analysis of Scheduling Processes in Road Intersections: Associating Deficiencies and Their Consequences in Colombian Projects - Karen Castañeda; Omar Sánchez; Carlos A. Peña; Rodrigo F. Herrera; Guillermo Mejía (Applied Sciences)
Road intersection projects are crucial for road infrastructure networks’ safe and efficient operation. Despite their importance, the construction of these projects faces significant challenges, such as delays, cost overruns, and litigation. Several causal factors for these phenomena have been identified as being associated with the construction schedule planning process. However, more studies need to be conducted to analyze the construction schedule planning process in detail. Therefore, the purpose of this paper is to analyze the schedule planning process of road intersection projects, emphasizing identifying and associating deficiencies in the planning process with their consequences on Colombian projects. The research method comprises three main stages: (1) identification of the schedule planning processes, (2) relation of the causes of deficiencies to the identified processes, and (3) analysis of the consequences of these deficiencies on the projects. A total of 29 schedule planning processes were identified, to which 22 causes of deficiency were assigned based on interviews with ten experts. The influence of these causes on schedule and budget deviations was analyzed based on the study of 25 Colombian road intersections. The results show that the lack of experience of the planner and poor estimation of material quantities strongly influence the generation of schedule and budget deviations in road intersection projects. Thus, this study contributes to improving the schedule planning process of road intersection projects by identifying the shortcomings and processes that can lead to schedule and budget deviations.